Komunikasi Pemimpin Pusat Daerah di Era Revolusi Industri 4.0 - Abdul Rani Usman; Azman Sulaiman; Teuku Zulyadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Communication between central-regional leaders is a substance in building the Indonesian nation. The central leaders, both the President, the Minister, as well as the first and second echelon officials based in Jakarta, need a strategy in communicating with regional leaders, both the Governor and the Regent. Regional leaders have problems communicating with central leaders due to different cultures, as well as the style of each region so that it becomes a challenge in communicating. This article examines how the Communication Between Central and regional leaders in the Revolutionary Era. The article used the Contingency Theory (Situational). The theory discusses maximum leadership quality in a particular place. The descriptive research method used is seeing an object, a set of conditions, thoughts or an event (Nazir, 1985: 63). The results study indicates that communication between regional central leaders depends on one's leadership style and depends on the leaders' strategies themselves.